(untitled) (The Strategic Review for Southern Africa, 2020)
Frantz Fanon, the Algerian theorist of revolution and social change, continues living through his profoundly luminous work that remains influential to the thinking and actions of many a people across the world even today. In Fanonian Practices in South Africa (2011), which comprises an introduction and five chapters, Nigel Gibson grapples with the important question of the relevance of Fanon's thought, 50 years after his death in 1961, to the South African situation especially from the time of Steve Biko to the time of the birth of the shack dwellers' movement, Abahlali baseMjondolo (Abahlali) in Durban on 19 March 2005. Gibson acknowledges that the idea of Fanonian Practices is not limited to South Africa but relevant also for other African countries. Elsewhere, Fanon's ideas have been exported to Black theology of liberation by scholars such as James Cone in the United States of America (USA) and Paulo Freire in Latin America.